2019
DOI: 10.1021/acs.molpharmaceut.9b00599
|View full text |Cite
|
Sign up to set email alerts
|

Design of N-Methyl-d-Glucamine-Based Resorcin[4]arene Nanoparticles for Enhanced Apoptosis Effects

Abstract: The addition of specific chemical groups in a macrocycle structure influences its functional properties and, consequently, can provide new possibilities, among which are aggregation properties, water solubility, biocompatibility, stimuli response, biological activity, etc. Herein, we report synthesis of new resorcin[4]­arene with N-methyl-d-glucamine groups on the upper rim and n-decyl chains on the lower rim, an investigation of its self-assembly behavior in aqueous media, and its use as a building block for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…With the addition of DTT, the polymer was reduced to 1. These results demonstrated that, different from the most reported examples that have explored delivery systems using a specific known macrocycle, 21,40,41 the 1 was actually a reactant that produced the self-assembling macrocycles with the DOX during the slowly oxidative process. Thermodynamics directed the synthesis of the right self-assembling macrocycles that can efficiently encapsulate the DOX molecules, giving rise to a high DLC.…”
Section: Resultsmentioning
confidence: 67%
“…With the addition of DTT, the polymer was reduced to 1. These results demonstrated that, different from the most reported examples that have explored delivery systems using a specific known macrocycle, 21,40,41 the 1 was actually a reactant that produced the self-assembling macrocycles with the DOX during the slowly oxidative process. Thermodynamics directed the synthesis of the right self-assembling macrocycles that can efficiently encapsulate the DOX molecules, giving rise to a high DLC.…”
Section: Resultsmentioning
confidence: 67%
“…The synthesized compound showed antimicrobial activity only against Gram-positive bacteria. Evaluating its cytotoxic effect on human erythrocytes, it is found that this macrocycle does not cause complete hemolysis, unlike other derivatives of the calixarenes family [27].…”
Section: Synthesis Of Calix[4]resorcinarenesmentioning
confidence: 99%
“…Calix [4]resorcinarene (C4RA) is one of the derivatives of C4A, made up of four resorcinol units connected by methylene bridges [ 56 , 57 ]. The substituent groups at the methylene bridges determine the conformers of C4RA, resulting in five stable isomers [ 56 , [58] , [59] , [60] , [61] , [62] ]. Modifying C4RA through various functional groups onto the eight hydroxyphenyl groups and aromatic rings provides a versatile platform for their multi-purpose use.…”
Section: Introductionmentioning
confidence: 99%